Take the 2-minute tour ×
Mathematica Stack Exchange is a question and answer site for users of Mathematica. It's 100% free, no registration required.

Consider the following:

a[m_, n_, x_] := 
    1/2^n (-1)^n/((2 n)!) Sum[Binomial[m, l] (m - 2 l)^(2 n), {l, 0, m}] x^(2 n)

a[m_, 0, x_] := 1

f[m_, x_] := Sum[a[m, n, x], {n, 0, Infinity}]

Indeterminate expression

I'm totally clueless why Mathematica fills in $0$ for $x$ while I feed it $x = 1$!

share|improve this question
    
Please also copy the code into the text editor so that we can more easily test your code. –  tkott Mar 11 '12 at 18:56
add comment

2 Answers 2

up vote 8 down vote accepted

Since you define f[m_,x_] by Sum[a[m,n,x],{n,0,Infinity}] so there are terms in the sum like 0^0 because :

a[0,n,1]=1/2^n ((-1)^n)/((2n)!) Sum[Binomial[0,l] (0-2l)^(2n),{l,0,0}] x^(2n)

When there is a[0,n,1] you start the sum with Sum[Binomial[0,l] (0-2l)^(2n),{l,0,0}] and the first term in the definition of f[m_,x_] is with n==0.

Edit

To prevent generating of messages one can define a[m,n,x] and f[m,x] this way :

a[m_Integer, n_Integer, x_] /; n > 0 := 
  1/2^n (-1)^n/((2 n)!) Sum[ Binomial[m, l] (m - 2l)^(2n), {l, 0, m}] x^(2 n)
a[m_Integer, 0, x_] := 1
f[m_Integer, x_] := Sum[ a[ m, n, x], {n, 0, Infinity}]
share|improve this answer
add comment

It is not because of x, but because the Sum in the definition of a.

In[12]:= Sum[Binomial[m, l] (m - 2 l)^(2 n), {l, 0, m}] /. m -> 0

Out[12]= 0^(2 n)
share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.